AIA Guide to Chicago - Petersen, Laurie McGovern; Sinkevitch, Alice (Book collections on Project MUSE., 2014)
"An unparalleled architectural powerhouse, Chicago offers visitors and natives alike a panorama of styles and forms. The third edition of the AIA Guide to Chicago brings readers up to date on ten years of dynamic changes with new entries on smaller projects as well as showcases like the Aqua building, Trump Tower, and Millennium Park. Four hundred photos and thirty-four specially commissioned maps make it easy to find each of the one thousand-plus featured buildings, while a comprehensive index organizes buildings by name and architect. This edition also features an introduction providing an indispensable overview of Chicago's architectural history."--